2004
DOI: 10.1081/ncn-200027469
|View full text |Cite
|
Sign up to set email alerts
|

Urate Oxidation in CSF and Blood of Patients with Inflammatory Disorders of the Nervous System

Abstract: Urate is largely excluded from the brain under non-inflammatory conditions (concentration gradient serum:CSF about 10:1), but increases markedly in Guillain-Barré Syndrome and bacterial meningitis. The oxidation product allantoin is normally not passively distributed between blood and cerebrospinal fluid (gradient 3:1) and increases 5-fold in CSF of patients with meningitis. Patients with multiple sclerosis had normal levels of urate and allantoin in blood and CSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Additionally, Becker et al found normal UA concentrations in blood and CSF of 18 patients with MS (33). In a recent study by Zamani et al (29), CSF and serum UA concentrations were measured in 12 patients with MS and 10 controls.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, Becker et al found normal UA concentrations in blood and CSF of 18 patients with MS (33). In a recent study by Zamani et al (29), CSF and serum UA concentrations were measured in 12 patients with MS and 10 controls.…”
Section: Discussionmentioning
confidence: 98%
“…[8]–[27] Furthermore, most of these studies [12], [16], [18][22], [25], [27] were conducted on small cohorts of MS patients and did not control urate levels for significant determinants of serum urate, particularly for renal function. Only one study [15] evaluated serum urate concentrations at the earliest stage of MS (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In the last ten years several studies evaluated serum urate levels in patients with MS, reporting conflicting results; [8]–[27] some case-control studies found lower, [8][15] but others reported higher [16][18] serum urate levels in MS patients than in neurological [16], [19], [20] and healthy controls [10], [16][19]; finally, other studies found no difference between the MS and neurological, [21], [22] and healthy controls. [23]–[27] A recent metanalysis was in favour of lower serum urate levels in MS than in healthy subjects and neurological controls [28] Furthermore, in a recent clinical trial, the combination of interferon beta and inosine was safe and well tolerated but did not provide any additional benefit on accumulation of disability compared with interferon beta alone.…”
Section: Introductionmentioning
confidence: 99%
“…Levels of serum urate are closely correlated with levels of urate in the cerebrospinal fluid (CSF) and CSF urate is typically 10% of peripheral levels. This suggests that CSF levels of urate are in part dependent on serum uric acid levels [7]. It has been suggested that uric acid may have neuroprotective influence as a scavenger of reactive nitrogen and oxygen radicals.…”
Section: Introductionmentioning
confidence: 99%